DETECTING THE ROLE OF QUINOA AGAINST THE TOXICITY OF HYDROGEN PEROXIDE, WHICH CAUSES DAMAGE TO TESTICULAR TISSUE, AND SOME PHYSIOLOGICAL PARAMETERS IN MALE RATS - Bayan M. Mahdi; Hiyam J. Ibrahim; Rajaa M. Ismail (PT. Antis International Publisher, 2024)
The current study aims to reveal the role of Quinoa seeds against the toxicity of hydrogen peroxide, which causes damage to testicular tissue and some physiological parameters in male rats. In this study 32 adult male albino rats, (wt 180-260 gm with age 3-5 month) obtained from Veterinary college/ Kirkuk University. the rats were randomly divided into four groups, control (n=8), and experimental (n=24) groups. The control group just received 4ml distilled water daily. However, the experimental groups divided into three groups each included 8 male albino rat. The findings showed that the concentration of testosterone (TE), follicle stimulating hormone (FSH) and luteinizing hormone (LH) in second group show significant (P